IDENTIFYING THE CORE DIMENSIONS OF BRAND AUTHENTICITY: A SYSTEMATIC LITERATURE REVIEW - Uysal, Adem (Pazarlama ve Pazarlama Arastirmalari Dernegi, 2025)
This study aims to examine both conceptual studies on the definition of brand authenticity and empirical research focused on scale development. Accordingly, the study seeks to identify the key dimensions of brand authenticity and provide an in-depth explanation of these dimensions. A systematic literature review method was employed in the study. In this study, a literature search was conducted in the Scopus, Web of Science, and Google Scholar databases to access relevant literature. As a result of the search, a total of 40 academic studies published between 2003 and 2024 were examined. The research findings indicate that both conceptual and empirical studies on brand authenticity address various dimensions of the concept. In this context, the literature's most frequently emphasized core dimensions include originality, heritage, credibility, sincerity, integrity, consistency, quality commitment, continuity, naturalness, and genuineness. This study provides significant contributions to both academic literature and practical applications. At the conceptual level, identifying the key dimensions of brand authenticity contributes to theoretical discussions. It serves as a guide for future empirical research and scale development studies across different sectors and consumer groups. From a managerial perspective, the study offers valuable insights for brand managers by highlighting the key elements they should focus on to enhance perceptions of authenticity.

Bu çalisma, marka özgünlügünün tanimlanmasina dair kavramsal düzeydeki çalismalarin yani sira, ampirik arastirmalar dogrultusunda gerçeklestirilen ölçek gelistirme çalismalarini incelemek amaciyla yapilmistir. Bu dogrultuda, marka özgünlügünün temel boyutlarinin belirlenmesi ve bu boyutlarin açiklanmasi hedeflenmistir. Bu çalismada, sistematik literatür taramasi yöntemi kullanilmistir. Çalismada, ilgili literatüre ulasmak amaciyla Scopus, Web of Science ve Google Akademik veri tabanlarinda tarama gerçeklestirilmistir. Tarama sonucunda, 2003–2024 yillari arasinda yayimlanmis toplam 40 bilimsel çalisma incelenmistir. Arastirma bulgulari, marka özgünlügüne iliskin hem kavramsal hem de ampirik çalismalarin farkli boyutlari ele aldigini ortaya koymaktadir. Bu baglamda, literatürde en sik vurgulanan temel boyutlarin orijinallik, miras, güvenilirlik, samimiyet, bütünlük, tutarlilik, kaliteye baglilik, süreklilik, dogallik ve gerçeklik oldugu belirlenmistir. Çalisma, hem akademik literatüre hem de uygulamaya yönelik katkilar sunmaktadir. Kavramsal düzeyde, marka özgünlügünün temel boyutlarinin belirlenmesi, ilgili teorik tartismalara katki saglarken, farkli sektörler ve tüketici gruplari baglaminda gelecekteki ampirik arastirmalara ve ölçek gelistirme çalismalarina rehberlik edebilecek niteliktedir. Yönetimsel açidan ise bu çalisma, marka yöneticilerine özgünlük algisini güçlendirmek adina odaklanmalari gereken temel unsurlari belirleme konusunda yol göstermektedir.
MARKA ÖZGÜNLÜGÜNÜN TEMEL BOYUTLARININ BELIRLENMESI: SISTEMATIK BIR LITERATÜR TARAMASI
Keywords: Product and Brand Management; Ürün ve Marka Yönetimi